315 Use of Flow Diverter in the Treatment of Anterior Communicating Artery Aneurysms: A Multicenter Experience (FEAR ME study). (April 2023) - Benalia, Victor; Cortez, Gustavo; Mounayer, Charbel; Saatci, Isil; Cekirge, Saruhan; Koçer, Nací; Islak, Civan; Dabus, Guilherme; Brinjikji, Waleed; Baltacıoğlu, Feyyaz; Pereira, Vitor Mendes; Nishi, Hidehisa; et al.
Abstract : INTRODUCTION: The anterior communicating artery (AcomA) is among the most common s ites of intracranial aneurysms and has an increased risk of rupture compared to other locations. The safety and efficacy of flow diverters utilization for aneurysm treatment have been demonstrated for many locations, less consistently for AcomA Complex. We present the most extensive analysis in the neurosurgical literature for flow diverter treatment in AcomA aneurysms. METHODS: Databases from nine centers were retrospectively reviewed for AcomA aneurysms treated with flow diverters. Demographic information, clinical presentation, radiographic characteristics, procedural complications, and post-procedure outcomes were obtained. RESULTS: A total of 181 patients harboring 186 AcomA aneurysms were treated between January 2012 to December 2021. Ninety-one were female (54.1%), median age was 61[51 – 68]. Most aneurysms were unruptured and located at the AcomA itself. Half of the cohort had similar anterior cerebral artery sizes (51.8%). The most common morphology was saccular (91.9%), with a branch involvement in 30.4% of cases. Median vessel diameter was 2.35 mm, and Pipeline Flex was the most prevalent device (39.8%). Median follow-up time was 16 months, with a complete occlusion rate of 85.6% in the last follow-up. Functional independence (mRS 0-2) was reported in 96.7% of patients at the last follow-up. Major complication rate was 2.2%, and mortality rate was 2.2% (4/181). CONCLUSIONS: Our results suggest that flow diverter is a useful tool as treatment modality for AcomA aneurysms. Mid-term results indicated favorable aneurysm occlusion rates and a lower complication rate. Additional prospective studies with longer follow-up and independent adjudication are warranted to assess these results better.